2016
DOI: 10.1073/pnas.1601294113
|View full text |Cite
|
Sign up to set email alerts
|

Multinational investigation of cross-societal cooperation

Abstract: In a globalized world, establishing successful cooperation between people from different nations is becoming increasingly important. We present results from a comprehensive investigation of crosssocietal cooperation in one-shot prisoner's dilemmas involving population-representative samples from six countries and identify crucial facilitators of and obstacles to cooperation. In interactions involving mutual knowledge about only the other players' nationalities, we demonstrate that people hold strong and transn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 47 publications
6
51
0
Order By: Relevance
“…We found that participants were more likely to invest in trustees from national groups perceived high in warmth and competence (in agreement with SCM predictions about the role of warmth and competence in inter-group social cognition; [ 19 , 56 ]). This finding is also in line with a recent work reporting that individuals have shared stereotypes in terms of expected cooperation for interaction partners from different countries and that these stereotype-driven expectations represent the strongest predictor of participants’ actual cooperation [ 70 ]. In addition, we showed that individual differences in Right-Wing Authoritarianism interacted with SCM social dimensions in shaping intergroup decision-making.…”
Section: Methodssupporting
confidence: 91%
“…We found that participants were more likely to invest in trustees from national groups perceived high in warmth and competence (in agreement with SCM predictions about the role of warmth and competence in inter-group social cognition; [ 19 , 56 ]). This finding is also in line with a recent work reporting that individuals have shared stereotypes in terms of expected cooperation for interaction partners from different countries and that these stereotype-driven expectations represent the strongest predictor of participants’ actual cooperation [ 70 ]. In addition, we showed that individual differences in Right-Wing Authoritarianism interacted with SCM social dimensions in shaping intergroup decision-making.…”
Section: Methodssupporting
confidence: 91%
“…Thus, at least some ingroup favoritism may be explained by a belief that people cooperate more with ingroup members. Furthermore, this belief generalized across all 17 countries and could not be explained by stereotypes of people from certain nationalities being more cooperative ( 28 ), and previous work suggests that the belief is not merely a byproduct of a positivity bias in thinking about ingroup members ( 29 ). Future research is necessary to understand the development and function of this belief in regulating cooperative interactions within and between groups.…”
Section: Discussionmentioning
confidence: 67%
“…Our findings generally support an in-between position taking into account both inherent factors and social influences as suggested by Social Role Theory. On the one hand, we observed a gap in transfers and expectations that remains stable when controlling for sender and receiver nations and additional factors that have been demonstrated to influence cross-national cooperation (Dorrough & Gl€ ockner, 2016; see Supporting Information, B3; Table B2) and that can also be observed for cooperation with a random interaction partner and the ingroup only. These results indicate some degree of universality in sex differences and, therefore, provide partial support for an evolutionary perspective assuming that those differences are a result of innate temperamental differences between men and women that evolved by natural selection (e.g., Buss & Kenrick, 1998).…”
Section: Discussionmentioning
confidence: 77%
“…It is even more pronounced when analysing transfers towards a random interaction partner only ( b = 6.89 US cents, p < .001). Furthermore, when controlling for additional factors, such as cultural similarity or spatial distance between nations that have been demonstrated to influence cross‐national cooperation (Dorrough & Glöckner, ), the effect also remains stable (Supporting Information, B3). These results speak for the fact that the observed gender differences are not (only) a result of specific country combinations.…”
Section: Resultsmentioning
confidence: 97%